1989
DOI: 10.2307/2328617
|View full text |Cite
|
Sign up to set email alerts
|

Original Issue High Yield Bonds: Aging Analyses of Defaults, Exchanges, and Calls

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and American Finance Association are collaborating with JSTOR to digitize, preserve and extend access ABSTRACT This paper presents an aging analysis of 741 high yield bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 3 publications
2
50
0
Order By: Relevance
“…This laborious process is necessary because of the lack of a centralized market and of information sources. To check for similarity of results, we compare our summary statistics for rated nonconvertible securities to those of Asquith, Mullins and Wolff (1989) and obtain similar results 3…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This laborious process is necessary because of the lack of a centralized market and of information sources. To check for similarity of results, we compare our summary statistics for rated nonconvertible securities to those of Asquith, Mullins and Wolff (1989) and obtain similar results 3…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies understate default rates because of the rapid increase in the par value of outstanding issues and because cumulative default rates increase with years from issuance. Two recent studies by Altman (1989) and Asquith, Mullins, and Wolff (1989) have corrected these problems by using aging analysis to follow rated nonconvertible high‐yield bonds over time; they find cumulative default rates for such bonds 10 years after issuance exceeding 30 percent.…”
mentioning
confidence: 99%
“…For example, Altman [1989] and Asquith, Mullins, and Wolff [1989] have found that the longer a high-yield bond is outstanding, the greater the likelihood of default. Lehman and Fridson [1995] have determined that high-yield debt with high coupon payments is more likely to default than similarly rated low-coupon debt.…”
Section: Default and Bankruptcy Literaturementioning
confidence: 99%
“…In millions of dollars. Source for totals: Asquith, Mullins, and Wolff (1989). Source for M&A related: Wigmore (1990).…”
Section: –1990: Leveraged Buyout and Divestiturementioning
confidence: 99%